A demand for wearable devices in health care - Vijayalakshmi, K.; Uma, S.; Bhuvanya, R.; Suresh, A. (International Journal of Engineering and Technology, 2018)
With the popularity of wearable devices, along with the development of telecommunication system there is a need for obtaining the health and fitness outcomes. So the recent advances in data analysis techniques have opened up new possibilities for using wearable technology in the digital health ecosystem. In past, it’s too difficult to use the wearable devices for healthcare system because of the size of those sensors. But now with front end amplification and wireless data transmission, the wearable devices are deployed in health monitoring systems. Although the devices are continuously monitoring the human’s body activity and collect various physiological data to increase the quality of human’s life. In this paper first we provide a research survey on available wearable or gadgets. Also we conclude with future directions in wearable research and market.